2020
DOI: 10.3390/ma13184007
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method to Prepare a Superhydrophobic Magnesium Alloy Surface

Abstract: The application of superhydrophobic materials has been handicapped by complex processes and poor environmental friendliness. Magnesium alloys are widely used in daily production due to their low density and good casting properties. A facile and environmentally friendly method was proposed to prepare a superhydrophobic layer with coral-like microstructure on the surface of AZ91D magnesium alloy by high temperature heating. The prepared superhydrophobic surface has a contact angle of 159.1° and a rolling angle o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…There exists a 'wide palette' of approaches on how to achieve a superhydrophobic surface [20], such as the sol-gel method, electrospinning, electrochemical methods, and layerby-layer method, which can be found in various review articles, like Darband et al [21] and Guo et al [22]. It has been confirmed that surfaces with hydrophobic properties can be an effective corrosion protection for numerous types of metal, such as steel [11,19,[23][24][25][26][27][28][29][30][31], copper [10,[32][33][34][35][36][37], nickel [38], zinc [39,40] Al-alloys [41][42][43][44][45][46] and Mg-alloys [47][48][49][50][51]. Carboxylic acids have been used to create hydrophobic surfaces on many different metal substrates [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…There exists a 'wide palette' of approaches on how to achieve a superhydrophobic surface [20], such as the sol-gel method, electrospinning, electrochemical methods, and layerby-layer method, which can be found in various review articles, like Darband et al [21] and Guo et al [22]. It has been confirmed that surfaces with hydrophobic properties can be an effective corrosion protection for numerous types of metal, such as steel [11,19,[23][24][25][26][27][28][29][30][31], copper [10,[32][33][34][35][36][37], nickel [38], zinc [39,40] Al-alloys [41][42][43][44][45][46] and Mg-alloys [47][48][49][50][51]. Carboxylic acids have been used to create hydrophobic surfaces on many different metal substrates [52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…There are important challenges for Mg-based implants if they are used in weight-bearing skeletal zones [ 160 , 161 ]. From a future perspective, the degradation of the Mg alloy orthopedic devices has to be optimized [ 162 , 163 , 164 ]. A cavity formation, surrounded by fibrous tissue near the implant site after its degradation, was observed; therefore, solutions such as inorganic or organic coatings applied on the Mg-based alloy surface should be considered in order to accurately control the degradation rate of the material.…”
Section: Clinical Translation Of Mg-based Materials For Temporary Imp...mentioning
confidence: 99%
“…A cavity formation, surrounded by fibrous tissue near the implant site after its degradation, was observed; therefore, solutions such as inorganic or organic coatings applied on the Mg-based alloy surface should be considered in order to accurately control the degradation rate of the material. Mg-based alloys exhibit insufficient mechanical strength for load-bearing applications, and a new implant design must be taken into account for these areas [ 164 ]. Sometimes, the breakage of the screw head can occur during the surgical procedures, and these unwanted events show that Mg implants must meet the demand of higher torque for future use in humans.…”
Section: Clinical Translation Of Mg-based Materials For Temporary Imp...mentioning
confidence: 99%
“…The interest in superhydrophobic materials has been rapidly growing and widely expanding into different application fields. 1 3 This is due to their ability to selectively repel water and hence enhance the performance of many systems whose applications involve a high degree of exposure to water. 4 , 5 Examples include self-cleaning, 6 , 7 drag reduction, 8 , 9 oil/water separation, 10 , 11 antifouling, 12 , 13 in addition to others.…”
Section: Introductionmentioning
confidence: 99%
“…The interest in superhydrophobic materials has been rapidly growing and widely expanding into different application fields. This is due to their ability to selectively repel water and hence enhance the performance of many systems whose applications involve a high degree of exposure to water. , Examples include self-cleaning, , drag reduction, , oil/water separation, , antifouling, , in addition to others. For many superhydrophobic coatings, water repellence is maximized when materials with low surface energy possess a surface structure with a high roughness, including micro/nano textures .…”
Section: Introductionmentioning
confidence: 99%